Emergence of carbapenem-resistant Acinetobacter baumannii as the major cause of ventilator-associated pneumonia in intensive care unit patients at an infectious disease hospital in southern Vietnam. - Nhu, N; Lan, N; Campbell, J; Parry, C; Thompson, C; Tuyen, H; Hoang, N; Tam, P; Le, V; Nga, T; Nhu, T; Van Minh, P; et al. (Society for General Microbiology, 2014)
Ventilator-associated pneumonia (VAP) is a serious healthcare-associated infection that affects up to 30 % of intubated and mechanically ventilated patients in intensive care units (ICUs) worldwide. The bacterial aetiology and corresponding antimicrobial susceptibility of VAP is highly variable, and can differ between countries, national provinces and even between different wards in the same hospital. We aimed to understand and document changes in the causative agents of VAP and their antimicrobial susceptibility profiles retrospectively over an 11 year period in a major infectious disease hospital in southern Vietnam. Our analysis outlined a significant shift from Pseudomonas aeruginosa to Acinetobacter spp. as the most prevalent bacteria isolated from quantitative tracheal aspirates in patients with VAP in this setting. Antimicrobial resistance was common across all bacterial species and we found a marked proportional annual increase in carbapenem-resistant Acinetobacter spp. over a 3 year period from 2008 (annual trend; odds ratio 1.656, P = 0.010). We further investigated the possible emergence of a carbapenem-resistant Acinetobacter baumannii clone by multiple-locus variable number tandem repeat analysis, finding a blaOXA-23-positive strain that was associated with an upsurge in the isolation of this pathogen. We additionally identified a single blaNDM-1-positive A. baumannii isolate. This work highlights the emergence of a carbapenem-resistant clone of A. baumannii and a worrying trend of antimicrobial resistance in the ICU of the Hospital for Tropical Diseases in Ho Chi Minh City, Vietnam.